Adhesion and Sliding Constitutive Relationship between Basalt–Polypropylene Hybrid Fiber-Reinforced Concrete and Steel Bars - Bo Wen; Guanyi Gao; Ding Huang; Hongyu Zheng (Applied Sciences, 2023)
The extreme marine environment of the South China Sea Islands, which features high temperatures, high humidity levels and high salt levels, seriously affects the safety of building structures. The durability of concrete can be significantly improved by adding a basalt–polypropylene hybrid fiber, but its bonding mechanism with deformed bars is complicated. Therefore, the bonding performance of hybrid basalt–polypropylene fiber-reinforced concrete and deformed bars was studied by combining experiments and a theoretical analysis. We designed 38 groups of different concrete strengths, different thicknesses of concrete covers, different anchor lengths and different diameters of rebars. The bond strengths, bond–sliding curves and failure forms of each pull specimen were compared and analyzed. The results showed that the failure forms and bond–slip curves of the basalt–polypropylene hybrid fiber-reinforced concrete specimens and the ordinary concrete specimens were essentially the same. Based on the results of the axial tensile tests, an ultimate bond strength prediction model was developed, and a bond–sliding constitutive model for hybrid fiber-reinforced concrete and steel bars was also established.